Histopathological Changes in Ewes Suffering from Emaciation and Cachexia Due to Certain Causes - Hyder Kareem Abbood (Basrah Journal of Veterinary Research)
This study was conducted to report the pathological changes in tissues taken from ewes suffering from emaciation and cachexia with referring to the most implicated possible diseases causing them, since emaciation lead to cachexia were the most devastating causes of life followed by economic losses in ewes has been planned and made.This scientific work was designed to collection samples with and histopathological study which were carried out on tissues in twenty old weak ewes purchased from local market in Amara city south of  Iraq. Tissue samples included multiple pieces of livers, lungs, and intestine which have been used in histopathological work. Results showed changes in all tissues taken from all animals of  the study ranged from thickening of the alveolar septa with interstitial hemorrhage and hyperplasia of bronchial epithelium in the lungs to complete atrophy of the intestinal villi, mucosal denudation, and mild mucosal inflammation in small intestine and mild bridging fibrosis in the centrilobular area in the liver. Results indicated that autopsied ewes had liver lesions occurrence 75%, intestinal lesion 70%, and lung lesion 65%, in all animals of the study , however within the same animals results were indicated that liver and lung lesions 60% , liver and intestinal lesions 55%, lung and intestine lesions 55%, and liver, lung and intestine lesions50%. It had been concluded from this study that aged cachectic and emaciated ewes have a dramatic pathological changes in their internal vital organs and tissues and the possible causes of these changes are an underling debilitating chronic disease states that render the affected animals weak and unhealthy animals.